A Convenient Synthesis of 4-amino-2-fluoro-N-methyl-benzamide. (October 2013) - Xu, Defeng; Xu, Xing; Zhu, Zhiling
A convenient and concise synthesis of 2-Fluoro-4-nitrobenzoic acid was obtained by oxidation of 2-fluoro-4-nitrotoluene with potassium permanganate in the presence of a phase transfer catalyst in 74% yield. N-methyl-2-fluoro-4-nitrobenzamide was then produced via chlorination and amination in 95% yield. Hydrogenation in the presence of Pd/C can afforded 4-amino-2-fluoro-N-methyl-benzamide in 98% yield